Hubungan Pergaulan Sosial Remaja dengan Motivasi Belajar Siswa di SMA Islam Al-Azhar NW Kayangan - Wawan Sukmawansyah (Universitas Pendidikan Mandalika, 2020)
The purpose of this study was to determine the relationship of adolescent social promiscuity with the learning motivation of Al-Azhar NW Kayangan Islamic High School students. The population of this research is all students in Al-Azhar NW Kayangan Islamic High School as many as 206 students. Sampling was carried out using Proportional Stratified Random Sampling with a total sample of 42 students. Data is collected using a questionnaire as the main method, documentation as a supplementary method. The research data were analyzed using product moment correlation analysis. The results showed that rhit of 0.621 was greater than rtab of 0.304 with a significance level (α) of 5% which meant that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Thus, the conclusion of the analysis in this study is that there is a relationship between adolescent social interaction with students' motivation to learn Al-Azhar NW Kayangan Islamic High School